IDENTIFIKASI HAMA TANAMAN KOPI DI KABUPATEN BANGKA TENGAH - Safitri, Novia; Zasari, Maera; Apriyadi, Rion (Universitas Lampung, 2025)
Coffee plants are one of the new commodities that are slowly being optimized by the Bangka Belitung Islands Province community, especially in Central Bangka Regency. In the production process, coffee plants have several obstacles, including pest attacks that can cause damage and reduce coffee production. This research needs to be conducted to identify the types of pests found in coffee plantations in Central Bangka as a basis for initial information to determine control measures. This study aims to identify the diversity and to determine the types of pests that most dominantly attack coffee plants in Central Bangka Regency. The research was conducted in April-July 2024; the research location was carried out in farmer's gardens in Celuak Village, Puput Village, Lampur Village, Munggu Village, Melabun Village, Jelutung Village and Lubuk Pabrik Village. Identification of pests that found at the research location was carried out at the Animal, Fish and Plant Quarantine Center Laboratory of the Bangka Belitung Islands. This research uses an exploration method and a survey technique. Determining the research location used the purposive sampling method and interviews with key informants through the Agricultural Extension Officer of Central Bangka Regency to obtain information about the criteria for coffee plant age ≥3 years. The sampling technique in this study was to determine the plot point (sample unit) using the simple random sampling method; 36 plants were taken in the research location. The results showed that the types of pests that attack coffee plants in Central Bangka Regency are Hypothenemus hampei, Ferrisia virgate, Dysmicoccus neobrevipes, Coccus viridis, Cephonodes hylas, Thosea vetusta, Xenocatantops humilis, snails, and rats with an average attack category of light to heavy. The type of pest with the highest percentage is the whitefly pest which attacks all coffee plantations used as research samples. The highest percentage of attacks is 43.42% and the intensity of attacks is 54.86%. Kata kunci: Attack percentage, attack intensity, coffee, pest identification